Coherence in a cold atom photon transistor - Li, Weibin; Lesanovsky, Igor (American Physical Society, 2015)
Recent experiments have realized an all-optical photon transistor using a cold atomic gas. This approach relies on electromagnetically induced transparency (EIT) in conjunction with the strong interaction among atoms excited to high-lying Rydberg states. The transistor is gated via a so-called Rydberg spinwave, in which a single Rydberg excitation is coherently shared by the whole ensemble. In its absence the incoming photon passes through the atomic ensemble by virtue of EIT while in its presence the photon is scattered rendering the atomic gas opaque. An important current challenge is to preserve the coherence of the Rydberg spinwave during the operation of the transistor, which would enable for example its coherent optical read-out and its further processing in quantum circuits. With a combined field theoretical and quantum jump approach and by employing a simple model description we investigate systematically and comprehensively how the coherence of the Rydberg spinwave is affected by photon scattering. With large-scale numerical calculations we show how coherence becomes increasingly protected with growing interatomic interaction strength. For the strongly interacting limit we derive analytical expressions for the spinwave fidelity as a function of the optical depth and bandwidth of the incoming photon.